ANALISIS TINGKAT KEAMANAN DAYA TARIK WISATA DEVIL’S TEAR NUSA LEMBONGAN - Pramesti, Kadek Ayu Dwi; Semara, I Made Trisna (Jurnal Analisis Pariwisata; Vol 19 No 01 (2019): Jurnal Analisis Pariwisata (2019), 2021)
This study examines tourist perceptions of safety in Devil’s Tear tourist attraction in Nusa Lembongan. The background of this research is Devil’s Tear is a place that many tourist visit in Nusa Lembongan. However, there are some incidents of tourist that died so the level of safety in this tourist attraction needs to be improved. The purpose of research is to determine the tourist’s perceptions about safety in Devil’s Tear tourist attraction in Nusa Lembongan. This type of research is quantitative descriptive. Data collection techniques used was a questionnaires with the number of sample is 60 tourists. Based on the results of the study concluded that the level of safety in Devil’s Tear tourist attraction included in the less secure category. This is due to the lack of tourism facilities that related to tourist safety and the lack of involvement from the management in maintaining the safety of devil’s tear tourist attraction. Keywords : Tourist attraction, Safety, Perception